Intervention research : from conceptualization to publication - Buono, Anthony F.; Savall, Henri; Cappelletti, Laurent (Emerald Publishing Limited : Information Age Publishing Inc., 2018)
This volume continues to build on the relationship between the Research in Management Consulting series and the intervener-researchers at the Socio-Economic Institute for Firms and Organizations (ISEOR) in Ecully, France, extending that partnership to our recent work with the French Foundation for Management Education (FNEGE), a foundation dedicated to closing the gap between the teaching and practice of management in France. As part of the Foundation's multifaceted activities--which range from seminars and an advanced training initiative for French doctoral students to joint programs with international organizations an associations--FNEGE partnered with ISEOR to sponsor a series of workshops on developing high quality intervention-research. This volume is one of the results from that endeavor.Although intervention-research helps to uncover valuable insight into organizational dynamics and performance, the challenge of capturing and disseminating that insight to both academics and practitioners is entrenched in the rigor-relevance debate. While we are witnessing increased calls for "actionable knowledge," this ideal, unfortunately, remains a rather elusive concept as critics contend either that rigorous academic research falls well-short of relevance to the practitioner world or research that proves to be valuable to practitioners falls short of the rigor expected in academic life. This volume is intended to help bridge that divide. Drawing on the FNEGE-ISEOR intervention-research workshop, the volume contains 18 chapters that explore the intervention-research process, from initial conceptualization, to implementation, to publication.The volume is published in French and English.
Keywords: Organizational change.; Organizational behavior.; Management -- Research.; Consultants.; Business & Economics -- Management.; Management and management techniques.; elektronické knihy; electronic books